Impact on ED Utilization and Associated Costs of Abortive Seizure Medications Using an Accountable Care Organization Database - Nunley, Sunjay; Cohen, Daniel M.; Cole, Justin; Patel, Anup D. (Journal of Pediatric Epilepsy, 2016)
Intranasal (IN) midazolam and per rectum (PR) diazepam abort seizures in the outpatient setting. IN midazolam is easier to use, has fewer side effects, and is more cost-effective than PR diazepam. The aim of this study is to determine if outpatient IN midazolam impacts emergency department (ED) utilization and health care costs compared with PR diazepam by utilizing a claims database. We retrospectively reviewed 5 years of data for 929 patients extracted from a claims database of an accountable care organization, Partners for Kids, whose population covers central and southeastern Ohio. Data elements consisted of demographics, ED visits, health care costs, and number of prescriptions. We found that using IN midazolam was not associated with increased ED utilization or increased health care costs. PR diazepam was associated with higher prescription costs. These findings support previous studies and show that both IN midazolam and PR diazepam are viable treatment options for patients at risk for prolonged seizures, but that IN midazolam is more cost-effective.
Keywords: per rectum diazepam; emergency department; intranasal midazolam